Accounting for housing in poverty analysis - Killian Mullan; Holly Sutherland; Francesca Zantomio (University of Essex, Institute for Social and Economic Research (ISER), 2009)
The treatment of housing in the definition of income used to measure poverty makes a big difference to who is counted as poor. Both the Before Housing Costs (BHC) and After Housing Costs (AHC) measures in current use in the UK pose problems. We compare BHC and AHC income with an alternative measure, overcoming their respective flaws by including in income the difference between the estimated value of housing consumed and housing costs, or net imputed rent. We investigate whether findings about poverty among children and pensioners, and the effectiveness of poverty-reducing policies, are affected by accounting for housing in this way.
Keywords: 330